2016
DOI: 10.17507/jltr.0704.09
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and English Language Learning at Iranian Grade One Senior High Schools: A Theoretical and Empirical Approach

Abstract: Abstract-This study aimed to explore whether the Parenting Authority Questionnaire (PAQ) relates significantly to the English language achievement of grade one senior high school (G1SHS) students in Mashhad, Iran. To this end, the PAQ designed by Buri (1991) was translated into Persian and administered to three hundred and nineteen students in two versions dealing with their fathers and mothers' parenting separately. Inspired by the microstructural approach of schema theory, the PAQ was treated as a measure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The last theme that was found is the Parenting style. Another factor related to English language learning has to do with parenting style wherein the "authoritative genus of both parents relates to students English learning achievement" (Khodadady & Hadizadeh, 2016). The results of the study carried out by the above-mentioned authors showed that not only the parenting domain but also its authoritarian, authoritative, and permissive genera correlate significantly with English achievement at different degrees.…”
Section: Parenting Stylementioning
confidence: 99%
“…The last theme that was found is the Parenting style. Another factor related to English language learning has to do with parenting style wherein the "authoritative genus of both parents relates to students English learning achievement" (Khodadady & Hadizadeh, 2016). The results of the study carried out by the above-mentioned authors showed that not only the parenting domain but also its authoritarian, authoritative, and permissive genera correlate significantly with English achievement at different degrees.…”
Section: Parenting Stylementioning
confidence: 99%
“…Bibi et al (2013, cited by Khodadady and Hadizadeh, 2016) explain that parenting is "a complex activity." This is so assumed because parents and other adults, including the kindergarten teachers, have to consider many aspects in doing the parenting since speaking in front of the children does not merely speak but also educate them.…”
Section: Parenting and Parenting Languagementioning
confidence: 99%